Robust machine-learning model for prediction of carbon dioxide adsorption on metal-organic frameworks; Journal of Alloys and Compounds; Vol. 1010 - Longe P. O. Promise; Davoodi Sh. Shadfar; Mehrad M. Mohammad; Wood D. A. David (2025, 2025)
Title screen